GR_GERICHTE ZF 2007 38 vom 20. November 2007 - GR Gerichte (2007)
Forderung aus Architektenvertrag (Haftung für Vertrauensschaden/Baukostenlimite/Baukostenüberwachung und -kontrolle) | OR Auftrag/Gesch\x27führung o. Auftrag/Bürgschaft etc. (OR 394-529)